Performance of selected casings as feed carrier for feeding of Asian buffalo leech Hirudinaria manillensis - Teh, Jun Chin; Kamarudin, Mohd Salleh; Abd Rahim, Abdullah; Saad, Che Roos; Fard, Ehsan Ramezani (Academic Journals, 2013)
Providing a suitable feeding delivery method is very important in the studies of the feeding behavior of medicinal leeches. In this study, several materials and membranes were tested for their suitability as blood carrier for the feeding of Asian buffalo leech Hirudinaria manillensis. In the first experiment, four different materials (sheep intestine skin, cotton wool, cellulose sausage casing and rubber sacs) were prepared and filled or soaked with pre-warmed cattle blood. The food was offered to leeches stocked in 10 L aquaria at 10 leeches per aquarium. All treatments were triplicated. The results showed that cotton wool and sheep intestine skin had severe blood leakage while cellulose sausage casing failed to allow leech feeding. Leeches successfully imbibed the blood with no visible leakage through the rubber sacs. In the second experiment, different solutions (150 mM sodium chloride, distilled water and 6 mg L-1 heparinized cattle blood) were prepared into rubber sacs. Similar feeding protocols as in the first experiment were followed. Percentages of leech that approached the sacs and the average volume consumed per individual were estimated. A little or no feeding response was observed for the sacs filled with saline and distilled water. This indicated H. manillensis were able to detect the blood contained in the rubber sacs and successfully imbibed the blood. Therefore, the rubber sac was found to be suitable as the blood carrier for the feeding of buffalo leeches.